2022
DOI: 10.1007/s00382-022-06640-3
|View full text |Cite
|
Sign up to set email alerts
|

High-latitude precipitation as a driver of multicentennial variability of the AMOC in a climate model of intermediate complexity

Abstract: Centennial-scale variability of the Atlantic Meridional Overturning Circulation (AMOC) in the absence of external forcing has been identified in several climate models, but proposed mechanisms differ considerably. Therefore, better understanding of processes governing AMOC variability at these timescales is needed. Here, we analyze numerical simulations with PlaSim-LSG, an Earth System Model Intermediate Complexity (EMIC), which exhibits strong multicentennial oscillations of AMOC strength under constant pre-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In climate science, the most interesting coupling is the master-slave coupling, which is particularly used to investigate tipping cascades in two or a few coupled natural systems (Klose et al, 2020;Wunderling et al, 2021;Kroenke et al, 2020). One example is the impact of the melting of the Greenland ice sheet on the AMOC (Mehling et al, 2022;Klose et al, 2023) or tipping in unidirectionally coupled networks (Kroenke et al, 2020). Additionally, we have studied mutually coupled systems where each subsystem is a driver for the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In climate science, the most interesting coupling is the master-slave coupling, which is particularly used to investigate tipping cascades in two or a few coupled natural systems (Klose et al, 2020;Wunderling et al, 2021;Kroenke et al, 2020). One example is the impact of the melting of the Greenland ice sheet on the AMOC (Mehling et al, 2022;Klose et al, 2023) or tipping in unidirectionally coupled networks (Kroenke et al, 2020). Additionally, we have studied mutually coupled systems where each subsystem is a driver for the other.…”
Section: Discussionmentioning
confidence: 99%
“…This bistability can give rise to a possible breakdown of the AMOC, which has been discussed employing several conceptual models (Stommel, 1961;Rahmstorf, 1996;Rooth, 1982;Wood et al, 2019) as well as in large ocean circulation models (Rahmstorf, 1995;Weijer et al, 2012). For the latter, it has been shown that the system is even multistable (Rahmstorf, 1995;Mehling et al, 2022) with different spatial patterns of heat transfer to the atmosphere. The possible melting of the Arctic Sea ice is also discussed in terms of bistability comprising two stable states in one of which the Arctic Sea ice disappears to a large extent in summer and shows ice cover only in winter (Notz, 2009;Eisenman and Wettlaufer, 2009;Eisenman, 2012), while the other corresponds to an ice cover for the whole year.…”
Section: Mechanisms Of Tipping and The Role Of Different Time Scalesmentioning
confidence: 99%
“…Those modes were attributed to Southern Ocean/Weddell Sea "flip-flop oscillations" driven by subsurface ocean heat content variations (52)(53)(54)(55)(56) or "loop oscillations," which are linked to the advection of salinity anomalies by the deep overturning (57)(58)(59)(60). Recent modeling studies suggested mechanisms of multicentennial AMOC variability driven by salinity anomalies that build up in the upper layers of the Arctic Ocean and are eventually released into the North Atlantic deep-water formation regions (61)(62)(63). By contrast, we found no role of the Arctic Ocean in driving the LGM multicentennial mode as variations in Arctic Ocean salinity and salinity fluxes out of the Arctic do not vary at this time scale (fig.…”
Section: Discussionmentioning
confidence: 99%
“…We perform numerical experiments using the Planet Simulator 33,34 General Circulation Model (PlaSim) coupled to the Large-Scale Geostrophic Ocean model (LSG) 36,36 . PlaSim-LSG, in different configurations, has been already used in several studies ranging from aquaplanets, to paleoclimatic reconstructions, future climate projections and AMOC variability 11,39,46 . PlaSim is based on the wet primitive equations representing the conservation of momentum and mass, the first law of thermodynamics and the equation of state, simplified by the hydrostatic approximation 34 .…”
Section: Methods the Climate Model: Plasim Coupled To Lsgmentioning
confidence: 99%
“…In particular, we focus on the atmospheric driving mechanisms, i.e exchanges of heat, fresh water and momentum as discussed in Gregory et al (2016) 21 , since it is the atmospheric state that drives climate variability in our rare events simulations (see Driving Mechanisms in Methods). The atmospheric internal variability is indeed a well-known key driver of interannual and multidecadal AMOC variability 11,[38][39][40][41][42][43][44] , via its impact on freshwater flux, heat exchanges and wind stress. However, its role in triggering abrupt changes or collapses of the AMOC is much less understood and atmosphere-ocean interactions that may prevent or favour the AMOC collapse have been both suggested 2,11,14,23 .…”
Section: Mechanisms For Amoc Slowdownsmentioning
confidence: 99%